The Use of Eco-Friendly Products in Indonesia: A Survey on Consumers Motivation - Nabiel Elhakim Al-Ahmad Bit; Mona Chaterina; Christian Haposan Pangaribuan (Journal of Applied Management Research, 2022)
The Use of Eco-Friendly Products in Indonesia: A Survey on Consumers Motivation. The use of products labeled as environmentally friendly is now on the rise in Indonesia. The use of products labeled as environmentally friendly is now on the rise in Indonesia. However, while the increasing sales of environmentally friendly products happen, public awareness of environmental sustainability has not yet improved. This paper aims to determine the factors that influence the rise of a trend, namely the use of environmentally friendly products, which has recently been rife in Indonesia. Thus, this study begins the investigation by distributing a questionnaire that uses quantitative methods and a Likert scale in data collection, with results coming from 63 Indonesian from various backgrounds. From the data, it can be concluded that of the three variables used, which are Environmental Awareness, FOMO (Fear of Missing Out), and Affordability, there is only one variable, FOMO that significantly influences the buyers’ motivation for eco-friendly products. Hence, FOMO should be considered an important aspect regarding marketing or campaign.